Coronavirus-19 pandemic and its impact on elective neurosurgical operations - Küçükyıldız, Halil Can; Şimşek, Salih Kürşat; Söylemez, Burçak; Güneş, Giray; Koç, Fatih; Özüm, Ünal (Journal of Surgery and Medicine, 2022)
Background/Aim: The Coronavirus-19 (COVID-19) pandemic disrupted all planned, elective surgical procedures and appointment-based health services due to the decreased capacity of hospitals, healthcare professionals' focus on fighting the pandemic and efforts to protect patients, society and healthcare workers from the pandemic. The purpose of this study was to ascertain the perspective of patients on elective surgery, who applied to neurosurgery outpatient clinics at two different centers as clean and non-clean hospitals. Methods: This cross-sectional prospective study was performed between March 2021 and July 2021, during the COVID-19 pandemic. 160 patients who were offered elective surgery for various indications in neurosurgery outpatient clinics were enrolled in the study. To this end, a questionnaire was administered to patients that included information about their demographics, pandemic processes and their anxiety levels during this process. Age, level of education, COVID -19 infection and vaccination status were all questioned in the survey. Univariate and multivariate analysis were used to determine the factors that might influence a patient's decision towards surgery. Results: In the univariate analysis of the factors, educational status, pandemic-induced anxiety and whether the hospital is a pandemic hospital or not were identified as statistically significant effective factors in patients' decision to accept surgery (P<0.05). Conclusion: We observed that the acceptance rate of patients for elective neurosurgical operations decreased during the pandemic period, but this situation was less felt in clean hospitals. We think that separating hospitals into two parts of clean and non-clean hospital is a beneficial health policy for the continuation of elective treatment procedures.